The Experiences of Nurses in Care Provision to COVID-19 Patients: A Qualitative Study - Mokhtari, Razieh; Yaghoobzadeh, Ameneh; Abdi, Kamel; Sajadi, Mahbobeh; Jaras, Mitra; Golitaleb, Mohamad (Frontiers in Public Health, 2022)
Introduction Nurses are key fighters in the forefront of care provision to COVID-19 patients. Due to the diversity of nurses' experiences in different countries because of variable nursing resources, health care systems, and cultural contexts, the present study aimed to divulge a deep understanding of the essence of health system problems based on nurses' experiences of care provision to COVID-19 patients in Iran. Methods The present study was conducted based on the conventional content analysis method and Graneheim & Lundman approach. The participants included the nurses working in the COVID-19 wards and were recruited by purposeful sampling and based on inclusion criteria. The data were collected by conducting semi-structured, one-to-one interviews, and taking field notes, until reaching data saturation. Results In-depth interviews with 12 nurses. represented four main categories and six subcategories. Sudden exposure to an unknown threat (nurses' feelings and concerns and nurses' reactions), being involved in an unequal war (a vicious virus and weary nurses), stressful working conditions, and efforts to confine the threat (seeking for new and adequate information and gathering all forces) were among the emerged data. Conclusion The nurses' experiences showed that despite passing a while since the coronavirus pandemic, there are still individual and professional concerns that all root in organizational and governmental factors.